The tracial topological rank of extensions of C^*-algebras - Hu, Shanwen; Lin, Huaxin; Xue, Yifeng (MATHEMATICA SCANDINAVICA, 2004)
Let 0→ J→ A→ A / J→ 0 be a short exact sequence of separable C^*-algebras. We introduce the notion of tracially quasidiagonal extension. Suppose that J and A/J have tracial topological rank zero. We prove that if (A, J) is tracially quasidiagonal, then A has tracial topological rank zero.